المنظومة القيمية في ظل تكنولوجيا الإعلام والاتصال الحديثة : الانترنت أنموذجا - لطرش، فيروز; العياشي، عيدوني (مؤسسة كنوز الحكمة للنشر والتوزيع, 2013)
تعتبر تكنُولوجيا الإعلام والاتّصال قِمّة التطّورات الحديثة، وتُمثل شبكة الانترنت كجزء منها قوة خلال تاريخ التطور البشري، فهي بناء ونسيج عالمي واسع الانتشار توفر معلومات وخدمات متنوعة في جميع مجالات الحياة، وهي وسيلة إعلامية اتصالية أزالت الحدود الجغرافية وقلّصت المسافات، وتُعتبر القيم الاجتماعية من أهم الثوابت والمبادئ الأساسية والمعايير التنموية في المجتمعات، فهي جزء من أجزاء تركيب وبناء المجتمع، وتلعب دوراً أساسيا في تكوين وتشكيل النسق الاجتماعي واستقراره، هذه القيم يكتسبها أفراد المجتمع من مؤسسات مختلفة داخل المجتمع، في ظل هذه المتغيرات واختلاف درجاتها من حيث التأثير أضحت التكنولوجيات الحديثة المتعددة الوسائط حتمية، خاصة منها شبكة الانترنت الوسيلة الأكثر انفتاحاً على العالم بما تملكه من تقنيات الجذب، خاصة في مجال الخدمات الاتصالية التكاملية التفاعلية، عن طريق البرامج والحجرات الحوارية المفتوحة للدردشة الشخصية والتعرف على الأصدقاء، والتي في أغلب الأحيان غير متجانسة في عملية التنشئة الاجتماعية.
The information and communication technology (ICT) represent a summit of the modern developments, and the internet as part of this modern developments consider a real power through the history of the human evolution, for the reason that it’s a build and a global groundwork well-known and widespread which offer and make available a lot of information’s and a variety of services in all sphere of life, it’s an instrument media of communication has removed the geographical boundaries and reduced distances, and the social values are considered us the most important constants and basic principles and standards development in the communities, because they are a part of the structural society and the construction of the community, and they play a key role in the formation and the creation of social pattern and in its stability, these values are getting by community members from different organizations inside the community, in light of these variables and there different degrees in terms of impact, the multimedia modern technologies has become inevitable, particularly the Internet the way more open to the world with its technical’s attraction, especially in the field of communication services which are complementary and interactive, through programs and rooms talk open to the personal chat and friends identification, which often is not homogeneous in the process of socialization development.
Keywords: الإنترنت -- القيم الاجتماعية -- تكنولوجيا الاتصالات -- وسائل الإعلام -- شبكات التواصل الاجتماعي